Bioactive Compounds and Antibacterial Activity of Red Beetroot (Beta vulgaris L.) Ethyl Acetate Extraction - Ida Bagus Gde Pranatayana; Immanuel Anthonio Caesebo Tampubolon; I Gede Putu Wirawan; I Nyoman Wijaya; I Ketut Suada; Khamdan Khalimi; I Kadek Wisma Yudha (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Red beetroot has been reported to possess various medicinal properties and antimicrobial activity. Therefore, this study aims to determine the compounds contained in the ethyl acetate extract of red beetroot pulp and evaluate its anti Escherichia coli effect. The extract was obtained by soaking the fruit in ethyl acetate, and then assessed for its components using GC-MS analysis. Antibacterial activity was tested using a disc diffusion assay. The results showed that the ethyl acetate extract of red beetroot pulp contained a total of 20 major compounds. These included ester of 1,3-benzenedicarboxylic acid and bis(2-ethylhexyl), 1,4-benzenedicarboxylic acid, and n-hexadecanoic acid. In the antibacterial test, the sample was highly effective against E. coli (IC 50 was 0,783 mg/mL). In addition, the diameter of the growth inhibition zone increased along with the extract concentration. These results suggest that the ethyl acetate extract of red beetroot pulp offers a natural antibacterial substitute to its synthetic equivalents.